Association of genetic variations with NAFLD in lean individuals. (12th October 2021) - Lin, Huapeng; Wong, Grace L.‐H.; Whatling, Carl; Chan, Anthony W.‐H.; Leung, Howard H.‐W.; Tse, Chi‐Hang; Shu, Sally S.‐T.; Chim, Angel M.‐L.; Lai, Jimmy C.‐T.; Yip, Terry C.‐F.; Wong, Vincent W.‐S.
Abstract: Background & Aims: How adiposity influences the effect of genetic variants on non‐alcoholic fatty liver disease (NAFLD) in the Asian population remains unclear. We aimed to study the association between genetic risk variants and susceptibility/severity of NAFLD in the lean, overweight and obese individuals. Methods: Nine hundred and four community subjects underwent proton‐magnetic resonance spectroscopy and transient elastography examination. Lean (<23 kg/m 2 ), overweight (23‐24.9 kg/m 2 ) and obesity (≥25 kg/m 2 ) were defined according to the body mass index cut‐offs for Asians. NAFLD was defined as intrahepatic triglycerides ≥5%. PNPLA3, TM6SF2, MBOAT7 and 9 other gene polymorphisms were analysed by rhAMP TM SNP assays. Results: Five hundred and twenty‐nine (58.5%), 162 (17.9%) and 213 (23.6%) subjects were lean, overweight and obese, respectively. The prevalence of NAFLD was 12.4%, 41.4% and 59.1% in the three groups ( P  < .001). Amongst those with NAFLD, lean subjects (30.3%) were more likely to carry the PNPLA3 rs738409 GG genotype than overweight (17.9%) and obese subjects (17.4%) ( P  = .003). Compared with the CC genotype, the GG genotype was associated with the greatest increase in the risk of NAFLD in lean subjects (odds ratio [OR] 6.04), compared with overweight (OR 3.43, 95% CI [1.06, 11.14]) and obese subjects (OR 2.51, 95% CI [0.93, 6.78]). Additionally, the TM6SF2 rs58542926 TT genotype was associated with reduced serum triglycerides only in lean subjects. A gene‐BMI effect was not observed for the other gene polymorphisms. Conclusions: The PNPLA3 rs738409 gene polymorphism has a greater effect on liver fat in Asian lean individuals than in overweight or obese ones.